Consumer’s attitude towards ready to eat food products in Klang Valley - Abdullah, Muhamad Amirul Ashraf (2018)
This study has been conducted in order to observe the consumer’s attitude towards ready to eat food products in Klang Valley. Since most of the consumers are having the busy lifestyle. They don’t have enough time to prepare the food for themselves. They prefer to buy the ready to eat food products which is more convenience. Despite of that, there are several problems that restraining them from buying the ready to eat food like the price and safety of consuming ready to eat food products. Still, there is also some problems about trust among consumer towards new kind of products. Using the simple random sampling method, a sample of 385 respondents was selected from multiple places in Klang Valley. The Klang Valley is chosen because the community consist of multiple races, ages, occupations and attitudes. Besides that, Klang Valley is chosen because this area are having high population density compared to the other places in Malaysia. Statistical methods like descriptive analysis, chi-square analysis and factor analysis were used in this research. In social demographic aspect, it is also found that most of the respondents are from urban area, single and age from 18 to 28 years old. It is also found most of consumer buy the ready to eat food because it is convenience and usually they buy it from supermarket and hypermarkets. Besides that, the consumers thinks the expiry date and halal certification becomes the most important factors that affect their attitude towards ready to eat food products. It also found that race, living area and salary have the association with consumer’s attitude towards ready to eat food products. The findings of this study shows that product attributes, health & safety concern and personal factor influencing the consumer’s attitude towards ready to eat food products. Understanding the attitudes of the consumer is challenging without the proper strategy. From this research, I certainly hoped that it can help marketers to plan their marketing strategies effectively. So, it can assist them perfecting their campaign and deepen marketing reach.